Leaning into Life: A Motion-Sensing Inquiry into Becoming InterActive for Life through Partnered Practices - Lloyd, Rebecca; Smith, Stephen (Université d'Ottawa | University of Ottawa, 2022)
What possibilities unfold when we explore what it means to not only become active but also inter-active for life? Does motional attunement show us how to live well with others beyond the practices at hand? We address these questions through partnered practices where postural attunements have particular significance. What our motion-sensing inquiry into AcroYoga, Push Hands Taijiquan, Salsa Dance, and Equestrian Arts reveals is that a bodily lean serves more than a functional purpose in creating connection. Various feelings and flows of responsiveness are experienced in the postural variations of leaning. This motion-sensing inquiry is intended to inspire movement practitioners, teachers and coaches, beyond the particular partnered practices studied, to consider how to attend more closely to the kinetic, kinesthetic and energetic dynamics of attuned responsiveness. Leaning into life can then be understood as a life-enhancing disposition that may be intentionally cultivated though a range of sustained and sustaining movement practices.
Keywords: posture; inter-action; flow; kinaesthetic awareness; partnered practices